2023
DOI: 10.2471/blt.22.288800
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer molecular diagnostics in Rwanda: a cost-minimization study of immunohistochemistry versus a novel GeneXpert® mRNA expression assay

Abstract: Objective To compare the financial and time cost of breast cancer biomarker analysis by immunohistochemistry with that by the Xpert ® STRAT4 assay. Methods We estimated costs (personnel, location, consumables and indirect) and time involved in breast cancer diagnosis at the Butaro Cancer Centre of Excellence, Rwanda, using time-driven activity-based costing. We performed a cost-minimization analysis to compare the cost of biomarker analysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A recent study compared the financial and time cost of BC biomarker analysis by IHC with that by the STRAT4 assay and concluded that BC biomarker analysis with STRAT4 has the potential to reduce the required human and capital resources in sub-Saharan African laboratories, leading to improved treatment selection and better clinical outcomes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared the financial and time cost of BC biomarker analysis by IHC with that by the STRAT4 assay and concluded that BC biomarker analysis with STRAT4 has the potential to reduce the required human and capital resources in sub-Saharan African laboratories, leading to improved treatment selection and better clinical outcomes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%